Excess adiposity and low physical fitness hamper Supine-to-Stand test performance among sedentary adolescents - Tadiotto, Maiara C. (2021)
The aim of this study was to analyze the relationship between body adiposity and physical fitness with performance in the Supine-to-Stand test (STS-test) in sedentary adolescents. Methods: Sixty-two adolescents, of both sexes, between 10 and 16 years old, participated in the study. Body mass (BM), height, waist circumference (WC), fat mass (FM), fat-free mass (FFM), right and left handgrip strength (HGS-right, HGS-left), abdominal resistance (ABDO), flexibility (FLEX), and cardiorespiratory fitness (VO2peak) were measured. Body mass index (BMI), z-score BMI (BMI-z), tri-ponderal mass index (TMI) and waist-to-height ratio (WHtR) were calculated. The STS-test was applied to evaluate the STS-MC by the movement patterns in the execution of the test. The STS-time in seconds (s) was categorized into terciles: fast (FG < 2.0 s), intermediate (IG = 2.0---2.6 s) and slow (SG > 2.6 s). One-way ANOVA, Chi-square, Spearman’s correlation coefficient as well as non-parametric tests were used, with significance p ≤ 0.05. Results: The SG presented higher BMI, BMI-z, TMI, WHtR, FM, %FM, as well as lower averages for %FFM, HGS-right, HGS-left, FLEX, ABDO, VO2peak, VO2peak relative to BM (VO2peakBM) in relation to GF. The BMI, BMI-z, TMI, WC, WHtR and FM showed moderate and direct correlations with STS-time and inverse with STS-MC (p < 0.01). HGS-right, HGS-left, ABDO, and VO2peakBM showed moderate and an inverse correlation with STS-time (p < 0.05). The VO2peakBM was moderate and with direct correlations to STS-MC (p < 0.01). Conclusion: It is concluded that excess fat and low physical fitness hamper STS-test perfor-mance. Therefore, the STS-test can be used for screening students to assess MC.Published by Elsevier Editora Ltda. on behalf of Sociedade Brasileira de Pediatria. This is anopen access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).